SEMIOTIKA PESAN DAKWAH DALAM LIRIK LAGU “IBU” KARYA HAJI IWAN FALS: STUDI DALAM PERSEPSI MAHASISWA IAI AL-AZIS - syarifudin, Ali; Sulistyani, Anjar; maulana, imang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research discusses the importance of understanding how students, as educated young generations, interpret the da'wah messages hidden in song lyrics. This study aims to analyze the da'wah messages contained in the lyrics of Haji Iwan Fals' song "Ibu" using Roland Barthes' semiotic approach, and to understand the perceptions of students at the Al-Zaytun Indonesia Islamic Institute towards these messages. The song "Ibu" was chosen because it contains strong moral and spiritual messages, especially regarding respect for parents, which is relevant to the values of Islamic teachings. The research method used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation. Roland Barthes' semiotic analysis was used to identify denotative, connotative, and mythical meanings in the song lyrics, while student perceptions were analyzed to see the extent to which da'wah messages were received and understood. The results of the study show that the lyrics of the song "Ibu" contain a strong da'wah message. This song depicts the love, sacrifice, and glory of a mother figure in an Islamic perspective. Students assess that this song is not only emotionally touching but also able to shape religious awareness and character values, especially in terms of respect for parents. This song is considered effective as a medium of cultural da'wah because it is able to convey religious messages through artistic and cultural approaches that are close to the community.